Development of Plywood Media into a Magic Drawer to Improve the Cognitive of Children Aged 4-5 Years at Birrul Walidain Kindergarten Gondangrejo Pekalongan East Lampung - Agustiningsih Agustiningsih; Leli Fertiliana Dea; Ferdian Utama (Bulletin of Early Childhood, 2025)
Birrul Walidain Gondangrejo Kindergarten, East Lampung, is an early childhood education institution that seeks to develop all aspects of child development, especially children's cognitive abilities through the use of concrete and interactive learning media. To optimize learning, it is necessary to add media with a new model so that the available teaching media is more maximal and varied. In this study, the "Magic Drawer" media was developed, where the term "magic" philosophically refers to a media that is able to foster curiosity, provide an interesting learning experience, and present educational surprises that stimulate the thinking skills of children aged 4-5 years. This research aims to develop plywood media into a "Magic Drawer" and find out its effectiveness in improving the cognitive abilities of children aged 4-5 years. The method used is Research and Development (R&D) with a 4D (Define, Design, Develop, Disseminate) model. Data collection techniques include observation, interviews, and documentation. The results of validation by material experts and media experts show that the "Magic Drawer" media is very suitable for use in early childhood learning. Trials limited to children aged 4-5 years showed an increase in cognitive abilities, such as recognizing colors, shapes, numbers, and the ability to group and think logically. Based on the results of quantitative and qualitative data analysis, the "MagicDrawer" media is effective and interesting to use in learning activities. Thus, plywood-based learning media developed into a "Magic Drawer" can be used as an alternative educational media to support the optimal improvement of children's cognitive abilities.